Investigation of the Mechanism of Anti-Inflammatory Action and Cytotoxicity of a Semipurified Fraction and Isolated Compounds From the Leaf of (Fabaceae) - Salmon A. Adebayo DTech; Helen C. Steel PhD; Leshweni J. Shai PhD; Jacobus N. Eloff DSc (SAGE Publishing, 2017)
Peltophorum africanum extracts have been shown to possess many important medicinal benefits, including anti-inflammatory and antiviral activities. However, the mechanism of action is poorly understood. The mechanism of anti-inflammatory action was determined by measuring the synthesis of cytokines in lipopolysaccharide (LPS) stimulated RAW 264.7 macrophage cells in vitro. Compound 1 (CP1), compound 2 (CP2), and fraction F3.3.0 (F3.3.0) significantly reduced the synthesis of interleukin 1β (IL-1β) from RAW 264.7 cells (1.18, 1.32, and 0.92 ng/mL), respectively. Similarly, CP1, CP2, and F3.3.0 inhibited the production of IL-2 and tumor necrosis factor-α (TNF-α) by RAW 264.7 cells (0.41, 0.60, 0.74 and 0.11, 0.27, 0.24 ng/mL, respectively. In addition, CP1 and CP2 had lower cytotoxicity toward RAW 264.7 cells, with CP2 indicating the lowest cytotoxicity (LD 50 = 207.88 µg/mL). The mechanism of action was found to be via the inhibition of pro-inflammation cytokines (IL-1 β and TNF-α). This observation may support the use of P africanum to treat pain-related conditions.